Early-onset prosthetic valve endocarditis caused by Inquilinus sp. - Pattarachai Kiratisin (2018)
Inquilinus is the newly described genus and has never been recognized as a cause of infective endocarditis. We report a case of early-onset prosthetic valve endocarditis caused by Inquilinus sp. in a tetralogy of Fallot patient who presented with heart failure. The bacterium was recovered from 11 consecutive blood cultures and identified by 16S rRNA gene sequencing. © 2006 Elsevier Inc. All rights reserved.